Development of the Acid-Base Module Based on Problem Based Learning with Ethnochemisty to Improve Students Science Literacy Ability - Puji Pebrianti; Andromeda; Yerimadesi; Hardeli; Okta Suryani (Postgraduate, University of Mataram, 2024)
This study aims to produce an acid-base module based on ethnochemical problem-based learning to improve students' scientific literacy skills, analyze the validity and practicality of the module and analyze the effectiveness of the acid-base module based on ethnochemical problem-based learning to improve students' scientific literacy skills. The type of research used is Research and Development (R&D) with a 4-D development model. The 4-D development model consists of 4 stages of development, namely define, design, develop and disseminate. The research instruments used are interview sheets, questionnaires, validation instruments, practicality instruments and effectiveness instruments. The validity test uses the Aiken's V formula. The results of the construct and content validity tests were 0.88 and 0.89 with a valid category. The results of the module practicality test carried out by teachers and students were 91.25% and 90.65% with a very practical category. The effectiveness test of the module was carried out using the N-Gain test and obtained a result of 0.71 in the high category. The results of the study indicate that a valid, practical and effective acid-base module based on ethnochemical problem-based learning has been obtained in improving students' scientific literacy skills.